Mortality in Correctional Institutions: Jail Populations, 2000-2017 ([Verlag nicht ermittelbar], 2021)
Mortality in Correctional Institutions (MCI)(formerly, the Deaths in Custody Reporting Program (DCRP)) is an annual data collection conducted by the Bureau of Justice Statistics (BJS). The MCI began in 2000 under the Death in Custody Reporting Act of 2000 (P.L. 106-297). It is the only national statistical collection that obtains detailed information about deaths in adult correctional facilities. The MCI collects data on persons dying in state prisons, local jails and in the process of arrest. Each collection is a separate subcollection, but each is under the umbrella of the MCI collection. This collection deals with the jail subcollection, which includes a jail populations file. The jail portion of Mortality in Correctional Institutions began in 2000 after the passage of the Deaths in Custody Reporting Act of 2000 in October of 2000. The original law lapsed at year-end 2006, but BJS continued to collect the data on a voluntary basis until the reauthorization of the Deaths in Custody Reporting Act in December of 2014. The jail component of the MCI collects data on the death of any inmate in his/her custody, even if the inmate was being held for another jurisdiction, such as the state department of corrections, another state or county, or the federal government. Jail deaths include the death of any inmate sent outside the jail facility for medical, mental health or substance abuse treatment services, or for work-release programs. Deaths that occur while an inmate is in transit to or from the jail facility are included. Deaths of jail inmates on temporary furloughs or who escaped from the jail facility are excluded. This longitudinal dataset includes year-end collections of population and admissions data from all jail jurisdictions nationwide annually, from 2000 to 2017. The file does not include death data. Interested users should see Mortality in Correctional Institutions: Local Jails, 2000-2017 (ICPSR 37878).